12 Effectiveness of simultaneous cardiac resynchronisation therapy in surgical valvular patients with severe heart failure. (9th April 2018) - Uchida, Tetsuro
Abstract : Background: Cardiac resynchronisation therapy (CRT) is an adjunct to medical therapy in managing severe heart failure (HF) patients. Despite advances in CRT, valvular heart disease (VHD) is currently a specific exclusion criterion and response to therapy in this setting remains unclear. This study aims to determine the effectiveness of CRT in HF patients undergoing valvular operation simultaneously. Methods: Between 2010 and 2016, 15 HF patients who underwent CRT in conjunction with valvular surgery were studied. Right and left ventricular and atrial epicardial leads were implanted after completion of valvular procedures. In patients with chronic atrial fibrillation (AF), Maze procedure was performed. To evaluate the improvement of ventricular mechanical dyssynchrony, echocardiographic assessment was repeated on admission and 1 month after CRT implantation. Results: There was no operative death. One patient with ischaemic cardiomyopathy died of sustained ventricular tachycardia two months after the operation. Post-operative course of severe HF patients was uneventful and all patients, except one, were discharged with improved NYHA class and ambulatory. Echocardiographic parameters of dyssynchrony did not reach statistical significance, but several parameters including LV-PEP and IVMD showing time delay of cardiac contraction, tended to be improve, suggesting contribution to the satisfactory post-operative course. Conclusions: The acceptable outcome was demonstrated with our concept to recover the intraventricular and atrio-ventrucular synchrony. Although difficult to establish the patient selection criteria for concomitant CRT and valvular surgery, our strategy is considered to be a feasible procedure to improve morbidity and mortality in patients with severe HF due to VHD.